f-Derivasi di BN1-Aljabar - Yanti, Rosa Gusmira; Handayani, Hanif; Fitria, Elsi (JOSTECH: Journal of Science and Technology, 2022)
In this paper, another type of derivation in BN1-algebra is defined, which involves an endomorphism of BN1-algebra, namely defining the concepts of left-right -derivation and right-left -derivation (briefly --derivation and --derivation) in BN1-algebras. Based on this definition, some properties of -derivation in BN1-algebras are constructed, then there is one common property, which is if Â is a (l, r)-f-derivation or a (r, l)-f-derivation of X, then Â is a f-derivation of X. Furthermore, some properties of a regular -derivation in BN1-algebras are constructed.